An Assessment of the Existence, Nature and Role of Current Internal Controls Being Applied at Lobels Bread, a Bread and Confectionary Manufacturer, Based in the Bulawayo Metropolitan Province in Zimbabwe - Tavarwisa, Kenneth (European Journal of Applied Sciences, 2026)
The research investigates and evaluates the existence, nature and role of internal controls at Lobels Bread Private Limited, a company facing financial distress, with the aim of identifying areas of weakness and providing recommendations to avoid and prevent collapse using a descriptive survey research design. The study employed questionnaires and interviews as tools for data collection, targeting 40 employees selected using stratified random sampling technique. The questionnaire consisted of both open- ended and closed- ended questions, while in-depth interviews were conducted with key personnel including the Finance Manager and Internal Auditor. The study reveals that Lobels Bread has a partially implemented internal control system with some controls in place but lacking comprehensiveness and effectiveness. The company’s control environment is characterized by inadequate segregation of duties, lack of clear policies and procedures, and insufficient monitoring and review processes. The study also identifies significant weaknesses in the company’s internal controls, including inadequate accounting and financial reporting systems, poor inventory management and lack of effective risk management policies. The findings of the study indicate that the internal controls at Lobels bread are not effective in preventing financial distress, and that the company is at risk of collapse if the weaknesses are not addressed. The study provide practical recommendations for Lobels bread to improve its internal controls , including strengthening the control environment , improving accounting and financial reporting systems, enhancing inventory management and establishing effective risk management processes. The study contributes to the existing literature on controls and financial distress, and provides insights into the importance of effective internal controls in preventing financial distress. The findings of this study are relevant to companies facing financial distress and can be used to inform strategies for improving internal controls and preventing collapse.